Alkyl Triarylstannanecarbodithioates: Synthesis, Crystal Structures, and Efficiency in RAFT Polymerization. Issue 63 (8th November 2017) - Kulai, Ihor; Saffon‐Merceron, Nathalie; Voitenko, Zoia; Mazières, Stéphane; Destarac, Mathias
Abstract: Eight alkyl triarylstannanecarbodithioates were synthesized starting from the corresponding triarylstannyl chlorides. They were fully characterized by IR and 1 H, 13 C, and 119 Sn NMR spectroscopy and mass spectrometry. Their solid‐state structures and geometric parameters were determined and compared to those of other classes of thiocarbonylthio compounds. These new organotin derivatives are efficient reversible chain‐transfer agents for reversible addition–fragmentation chain transfer (RAFT) polymerization of styrene (St) and n ‐butyl acrylate (BA), with controlled number‐average molecular weights and narrow dispersities ( Ð <1.3). In some cases, loss of control of the polymerization was evidenced and supported by the observation of side products by 119 Sn NMR spectroscopy. This phenomenon was attributed to the thermal instability of the Sn‐RAFT terminal group. Abstract : Tin RAFTing : A series of triarylstannanecarbodithioates was synthesized. The presence of bulky and strongly electron positive tin makes them highly reactive reversible addition–fragmentation chain‐transfer agents in the free‐radical polymerization of styrene and n ‐butyl acrylate (see figure). 119 Sn NMR spectroscopy allows monitoring of their transformations during polymerization.